2022
DOI: 10.34172/hpp.2022.11
|View full text |Cite
|
Sign up to set email alerts
|

Problematic versus reflective use: Types of social media use as determinants of mental health among young Filipino undergraduates

Abstract: Background: The link between problematic social media use (SMU) and mental health among youth has been established. However, there is insufficient information on how mental health is influenced by COVID-19 pandemic-related changes and positive aspects of SMU. This study aims to determine the relationship of pandemic-related changes in SMU, and two types of SMU (problematic and reflective use) with mental health among young Filipino undergraduates. Methods: A total of 1087 Filipino undergraduates aged 18 to 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 42 publications
(51 reference statements)
1
8
0
Order By: Relevance
“…Moreover, the present study indicates that LGBTQ+ respondents demonstrated poor bidimensional mental health outcomes compared to cisheterosexuals. This corroborates the previous studies conducted pre‐COVID (Alibudbud, 2021) and during lockdown (Alibudbud, 2022a, 2022b; Cleofas et al., 2022) that suggests that Filipino non‐cisgender and non‐heterosexual youth were of greater risk for poor mental well‐being, and higher depression, stress and anxiety. The gender landscape of the Philippines is highly influenced by Catholic dogma; hence, cishetero‐patriarchal discourses permeate all social institutions in the country and rationalize structural violence against LGBTQ+ Filipinos (United Nations Development Programme, 2015).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Moreover, the present study indicates that LGBTQ+ respondents demonstrated poor bidimensional mental health outcomes compared to cisheterosexuals. This corroborates the previous studies conducted pre‐COVID (Alibudbud, 2021) and during lockdown (Alibudbud, 2022a, 2022b; Cleofas et al., 2022) that suggests that Filipino non‐cisgender and non‐heterosexual youth were of greater risk for poor mental well‐being, and higher depression, stress and anxiety. The gender landscape of the Philippines is highly influenced by Catholic dogma; hence, cishetero‐patriarchal discourses permeate all social institutions in the country and rationalize structural violence against LGBTQ+ Filipinos (United Nations Development Programme, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, female college respondents demonstrated poorer mental health outcomes than males, which is consistent with pre‐COVID research linking being female as a risk for low mental well‐being (Madden, 2010) and high psychological distress (Miranda‐Mendizabal et al., 2019). Moreover, a study conducted during pandemic‐related lockdown in the Philippines also indicates significantly poorer mental well‐being among female university students (Cleofas et al., 2022). This gender disparity in mental health vulnerability may be attributed to the stressors related to being a young female in the Philippines, whose likelihood of exhibiting anxiety and depression is linked with experiences of gender inequality, as evinced by prior research (Alibudbud, 2022b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, research on the role of seeking and receiving social support online on mental health outcomes remains to be unclear, as suggested by Chang et al (2022). The Philippines is often described as a collectivist culture (Flaming et al, 2010); hence, we argue that online social support is a potential salient mediator between Internet use and mental health, especially during the time of the pandemic, when Filipino students have become more reliant on Internet technologies to meet their social and intimacy needs due to COVID-induced physical distancing (Cleofas et al, 2022b). In this study, online social support is characterized as the experiences of students in socializing online in order to access benefits and fulfill their emotional, informational, companionship, and instrumental needs.…”
mentioning
confidence: 81%
“…Particularly in the Philippines, Christianity remains to be a strong cultural force that reproduces cisheteropatriarchy that maintains the structural violence that threatens the human security of queer Filipinos ( Manalastas and Torre, 2013 ), as evidenced by increased vulnerability to psychological issues (e.g., Cleofas et al, 2022 ). Queer emerging adults may experience a lack of fair access to work, education, and health care, fear of rejection from family and other social groups, and increased vulnerability to mental health concerns ( Salvatore and Daftary-Kapur, 2020 ).…”
Section: Introduction: Queering Human Security In Emerging Adulthoodmentioning
confidence: 99%